Pengaruh Pemberian Pempek Tepung Jamur Tiram Putih (Pleurotus Ostreatus) terhadap Penurunan Kadar Kolesterol Total di Puskesmas Taman Bacaan Palembang. - Putri, Thasya Namira; Sartono, Sartono; Yulianto, Yulianto (Jurusan Gizi, Poltekkes Kemenkes Palembang, 2024)
Background: Hypercholesterolemia is a condition in which cholesterol levels in the blood exceed the normal limit, which is > 200 mg/dl. Factors that cause hypercholesterolemia are lack of exercise, age, family history, and eating habits. Purpose: is to see the effect of giving white oyster mushroom flour(Pleurotus Ostreatus) pempek to reduce total cholesterol levels at Taman Bacaan Public Health Center Palembang. Methods: This research used pure experiment design. The design of this study used pre-test and post-test design with a control group. The total population of this study was 364 people, obtained a sample of 78 people. Results: of the results of the t-dependent test that the average cholesterol levels in the treatment group before the intervention was 252.62 mg/dl, while the average total cholesterol level after the intervention for 21 consecutive days was 204.36 mg/dl. In the control group before the intervention was 250.77 mg/dl, while after the intervention it was 230.33 mg/dl with a p-value of 0.000. Conclusion: Pempek white oyster mushroom flour has an effect on reducing total cholesterol levels with the difference in the treatment group being 48.28 mg/dl and the control group 20.44 mg/dl.